Thai enthusiast community among indonesian youth - Resti Candra Suci; Sahruman Sahruman (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the emergence of Thai popular culture among Indonesian youth through the Thai Enthusiast (Thai Enthu) community, a digital fan-based group centered on T-pop, Thai series, and social media platforms such as TikTok and YouTube. Using Henry Jenkins’ Participatory Culture Theory, this qualitative study explores how community members act as active participants who share, discuss, and interpret Thai cultural content rather than as passive consumers. The study addresses two research questions: how the Thai Enthusiast community spreads Thai culture in Indonesia, and what factors make Thai culture popular among Indonesian youth. Data were collected through observation of Thai-related content on TikTok and YouTube, as well as interactions within Thai Enthusiast community groups. The findings show that the community spreads Thai culture through content sharing, participation in viral trends, cultural translation and adaptation, member interaction, and the network effect of social media algorithms. The popularity of Thai culture among Indonesian youth is driven by strong social media exposure, an attractive entertainment industry, relatable storytelling, and the active role of fan communities. This study concludes that the Thai Enthusiast community functions as a vital agent of cultural exchange, introducing Thai language, food, fashion, and lifestyle to Indonesian audiences while reinforcing participatory fan culture in the digital era.